Fisetin, a dietary flavonoid induces apoptosis via modulating the MAPK and PI3K/Akt signalling pathways in human osteosarcoma (U-2 OS) cells - Li, Jian-Ming; Li, Wu-Yin; Huang, Man-Yu; Zhang, Xiao-Qiang (Bangladesh Journal of Pharmacology, 2015)
Human osteosarcoma is the most prevalent primary malignant bone tumor with high frequency of invasion and metastasis. Strong resistance coupled with toxicity of the currently available chemotherapeutic drugs poses challenge in treatment. The study aimed to investigate if fisetin, a dietary flavonoid induced apoptosis in human osteosarcoma (U-2 OS) cells. Fisetin at 20-100 µM effectively reduced the viability of OS cells, and induced apoptosis by significantly inducing the expression of caspases (Caspases- 3,-8 and -9) and pro-apoptotic proteins (Bax and Bad) with subsequent down-regulation of Bcl-xL and Bcl-2. While fisetin inhibited PI3K/Akt pathway and ERK1/2, it caused enhanced expressions of p-JNK, p-c-Jun and p-p38. Fisetin-induced ROS generation and decrease in mitochondrial membrane potential would have also contributed to rise in apoptotic cell counts. The observations suggest that fisetin was able to effectively induce apoptosis of U-2 OS cells through ROS generation and modulation of MAPK and PI3K/Akt signalling cascades.